Hollywood quarterly : film culture in postwar America, 1945-1957 - Smoodin, Eric Loren; Martin, Ann, 1940- (Berkeley, California : University of California Press, 2002)
The first issue of Hollywood Quarterly, in October 1945, marked the appearance of the most significant, successful, and regularly published journal of its kind in the United States. For its entire life, the Quarterly held to the leftist utopianism of its founders, several of whom would later be blacklisted.
Introduction : The Hollywood Quarterly, 1945-1957 / Eric Smoodin -- Part 1. The Avant-Garde -- Experimental Cinema in America, Part One : 1921-1941 / Lewis Jacobs -- Experimental Cinema in America, Part Two : The Postwar Revival / Lewis Jacobs -- The Avant-Garde Film Seen from Within / Hans Richter -- Cinema 16 : A Showcase for the Nonfiction Film / Amos Vogel -- Part 2. Animation -- Animation Learns a New Language / John Hubley and Zachary Schwartz -- Music and the Animated Cartoon / Chuck Jones -- Notes on Animated Sound / Norman McLaren -- Mr. Magoo as Public Dream / Milton J. Rosenberg -- Part 3. Documentary -- Postwar Patterns / John Grierson -- The Documentary and Hollywood / Philip Dunne -- Time Flickers Out : Notes on the Passing of the March of Time / Raymond Fielding -- Part 4. Radio -- The Case of David Smith : A Script, with Commentary by Sam Moore, Franklin Fearing, and Cal Kuhl / Abraham Polonsky -- Radio's Attraction for Housewives / Ruth Palter -- A New Kind of Diplomacy / Gene King -- Part 5. Practice -- A Costume Problem : From Shot to Stage to Screen / Edith Head -- Performance under Pressure / Alexander Knox -- Designing The Heiress / Harry Horner -- The Limitations of Television / Rudy Bretz -- Part 6. Television -- Hollywood in the Television Age / Samuel Goldwyn -- You and Television / Lyman Bryson and Edward R. Murrow -- Children's Television Habits and Preferences / May V. Seagoe -- How to Look at Television / T.W. Adorno -- Part 7. The Hollywood Picture -- Why Wait for Posterity? / Iris Barry -- Hollywood : Illusion and Reality / John Howard Lawson -- Negro Stereotypes on the Screen / Leon H. Hardwick -- Today's Hero : A Review / John Houseman -- An Exhibitor Begs for "B's" / Arthur L. Mayer -- A Word of Caution for the Intelligent Consumer of Motion Pictures / Franklin Fearing -- There's Really No Business Like Show Business / Jay E. Gordon -- There's Still No Business Like It / Jean Hersholt [and others] -- Hollywood's Foreign Correspondents / Harva Kaaren Sprager -- Part 8. Scenes from Abroad -- Advanced Training for Film Workers : Russia / Jay Leyda -- Advanced Training for Film Workers : France / Charles Boyer -- The Global Film / Vsevolod Pudovkin -- The Postwar French Cinema / Georges Sadoul -- When in Rome ... / Hugh Gray -- Part 9. Notes and Communications -- J'Accuse / Pierre Descaves -- Je Confirme / Robert Joseph -- The Cinémathèque Française / Henri Langlois -- Jean Vigo / Siegfried Kracauer -- Two Views of a Director-- Billy Wilder / Herbert G. Luft and Charles Brackett -- Dialogue between the Moviegoing Public and a Witness for Jean Cocteau / Raymond Jean.
Includes bibliographical references and indexes.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Motion pictures -- United States; Cinéma -- États-Unis.; PERFORMING ARTS -- Film & Video -- Reference; PERFORMING ARTS -- Film & Video -- General; Motion pictures; United States; Humaniora -- Film; Motion pictures; Motion pictures; Films